2016
DOI: 10.1112/jlms/jdw049
|View full text |Cite
|
Sign up to set email alerts
|

Band surgeries and crossing changes between fibered links

Abstract: We characterize cutting arcs on fiber surfaces that produce new fiber surfaces, and the changes in monodromy resulting from such cuts. As a corollary, we characterize band surgeries between fibered links and introduce an operation called Generalized Hopf banding. We further characterize generalized crossing changes between fibered links, and the resulting changes in monodromy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The same research group later showed that the XerCD-dif -FtsK enzymatic complex could unlink replication links tied in vivo in E. coli cells deficient in the decatenase topoIV [33]. Several groups of authors, including our own, studied mathematically the mechanism and pathways of DNA unlinking by site-specific recombination [12,13,83,85]. In [83] we showed that at least 2m steps are needed to unlink a replication link of type T (2, 2n) with one recombination site in each component in the orientation indicated in Figure 3.…”
Section: 3mentioning
confidence: 98%
See 2 more Smart Citations
“…The same research group later showed that the XerCD-dif -FtsK enzymatic complex could unlink replication links tied in vivo in E. coli cells deficient in the decatenase topoIV [33]. Several groups of authors, including our own, studied mathematically the mechanism and pathways of DNA unlinking by site-specific recombination [12,13,83,85]. In [83] we showed that at least 2m steps are needed to unlink a replication link of type T (2, 2n) with one recombination site in each component in the orientation indicated in Figure 3.…”
Section: 3mentioning
confidence: 98%
“…We identified minimal pathways of unlinking under a variety of biologically-motivated assumptions and used the transition probabilities obtained numerically to identify a most probable minimal pathway of DNA unlinking of replication links. In [12], the authors characterize coherent band pathways between knots and two-component links of small crossing number, and in [13], they characterize band surgeries between fibered links in terms of arcs on the fiber surfaces of such links. The above-mentioned studies were all concerned with site-specific recombination modeled as coherent band surgery, and point to the T (2, n) torus knots and links as having heightened importance in pathways of unlinking of replication links.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 10. Coherent band surgery is better understood than the non-coherent case (see for example [37,38,13,14,21,64]). If a coherent band surgery decreases the maximal Euler characteristic of an oriented surface without closed components bounding the link, it is known that the band can be isotoped to lie onto a taut Seifert surface [62], [35,Theorem 1.6].…”
Section: Relevance Of Theorem 11 and Corollary 12 To Dna Topologymentioning
confidence: 99%
“…If the linking number is instead −n/2, Corollary 1.2 follows from the characterization of coherent band surgeries between T (2, n) torus links and certain two-bridge knots in [21,Theorem 3.1]. While both coherent and non-coherent band surgeries have biological relevance, more attention in the literature has been paid to the coherent band surgery model (see for example [37,21,64,38,13,14,67]). This is due in part to the relative difficulty in working with non-orientable surfaces, as is the case with non-coherent band surgery on knots.…”
Section: Introductionmentioning
confidence: 99%